ISLAMIST MOBILIZATION UNDER ARAB SPRING: A CASE STUDY OF EGYPT - Ahmad, Mohammad Wasim (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The uprising that started in December 2010 commonly referred to as the Arab Spring, was an era of massive transformation in the political climate, the society and culture of the Arab world. It refers to a set of actions against the authorities in many states of the Middle East and North Africa, including protests, uprisings and revolutions. The aftermath of such uprisings included changes of regime within some of these nations while others degenerated into wars. Among the participants of these protests and uprisings, there were Islamist organizations, whose actions, ideology, and influence were the issues dominating the events that-centred around such countries as Egypt. Drawing on the Arab Spring of 2012 in Egypt, this paper seeks to advance understanding of Islamist mobilization with a view to presenting elaborate analyses of political, social, and religious mobilization. Egypt is one of the leading and influential Arab states that can give readers a comprehensive insight into the relation between Islamism, politics and revolution.